Audit of Diagnosis of Gonococcal Infection in a Genito Urinary medicine (Gum) clinic - Naeem, Sartaj; Khattak, M. N. (Journal of Postgraduate Medical Institute, 2011)
to study the efficacy of Gram stained smear in screening cases of gonorrhea and comparing its sensitivity with culture of N Gonorrhea.